2020
DOI: 10.1109/access.2019.2958337
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Agile-Beam NOMA in Millimeter Wave Networks

Abstract: We propose an agile-beam non-orthogonal multiple access (NOMA) scheme for millimeter wave (mmWave) communication networks. The agile-beam NOMA scheme flexibly switches between the single/multi-beam NOMA depending on the user pairing results. In particular, a novel user pairing strategy employing both distance and angle information is designed to facilitate the agile-beam NOMA transmission. More specifically, the base station first selects one user from the far user group randomly and then pairs it with the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Comparative analysis of the Outage probability for downlink NOMA-mmWave network over small-scale fading channels concluded that NOMA outperforms OMA in multi-cell-based mmWaves systems [225]. [226] suggested application of agile beam NOMA for mmWave networks and observes that NOMA-mmWave has better coverage probability and sumrate than OMA mmWave networks. Compared with TDMA based MIMO-mmWave networks for D2D communications, for NOMA-based MIMO-mmWave networks, Outage Probability tends to decrease exponentially, whereas ergodic capacity increases linearly [227].…”
Section: F Mmwave Communicationmentioning
confidence: 99%
“…Comparative analysis of the Outage probability for downlink NOMA-mmWave network over small-scale fading channels concluded that NOMA outperforms OMA in multi-cell-based mmWaves systems [225]. [226] suggested application of agile beam NOMA for mmWave networks and observes that NOMA-mmWave has better coverage probability and sumrate than OMA mmWave networks. Compared with TDMA based MIMO-mmWave networks for D2D communications, for NOMA-based MIMO-mmWave networks, Outage Probability tends to decrease exponentially, whereas ergodic capacity increases linearly [227].…”
Section: F Mmwave Communicationmentioning
confidence: 99%
“…8. A certain number of adjacent antennas are separated in a group to form multiple sub-arrays that can generate analog beams steering to desired users [35], [36]. With different numbers of sub-arrays, the number of beams can be adjusted flexibly.…”
Section: A New Beamforming Technologiesmentioning
confidence: 99%
“…For convenience, we set κ t = [K t , m t , ∆ t , σ t ] (t ∈ {p, q}) and a = 0.2 for all the simulations under GPA scheme. (2) and (3) shows that the SINR of the two users under GPA scheme is only affected by their own channel fading. Figs.…”
Section: B the Impact Of Ftr Channel Parametersmentioning
confidence: 99%
“…In [2], the OP of downlink NOMA in multi-cell mmWave networks was studied over Nakagami-m fading. In [3], coverage probability and sum rate of agile-beam NOMA were investigated in mmWave networks over singlepath channels. In [4], the coverage probability, the average number of served users, and the sum rate of NOMA were studied for the cooperative multicast mmWave wireless networks over Nakagami-m fading channels.…”
Section: Introductionmentioning
confidence: 99%